2011
DOI: 10.1007/s00417-011-1873-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of 50 eyes with long-term silicone oil tamponade for more than 12 months

Abstract: Long-term silicone oil can be a last-resort option in selected patients with severe vitreoretinal disease. Anterior and posterior segment complications did occur at significant rates. Forty percent of our patients maintained ambulatory vision. The actual number of patients that achieved satisfactory stereopsis and benefited functionally from long-term SO was much less [7/50 (14%)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
4
49
1
3
Order By: Relevance
“…Pseudomonas aeruginosa can cause ocular or periocular infections, such as keratitis, conjunctivitis, and dacryocystitis. 1 There have been reports of periocular and eyelid necrotizing fasciitis secondary to Pseudomonas infection and these cases are usually accompanied by systemic illness, malnutrition, alcoholism, or minor ocular trauma. 2 Typically, bilateral ocular involvement and neutropenia is seen.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa can cause ocular or periocular infections, such as keratitis, conjunctivitis, and dacryocystitis. 1 There have been reports of periocular and eyelid necrotizing fasciitis secondary to Pseudomonas infection and these cases are usually accompanied by systemic illness, malnutrition, alcoholism, or minor ocular trauma. 2 Typically, bilateral ocular involvement and neutropenia is seen.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…1 It is most frequently indicated in complex cases of retinal detachments and proliferative diabetic retinopathy associated with tractional retinal detachment, as well as ocular trauma to stabilize the retina and inhibit proliferative activity. 1 Liquid silicone was first injected into the vitreous cavity of rabbit eyes in 1958, and then utilized for the treatment of retinal detachments in 1962 by Cibis et al 2 Several complications have been reported: including cataract formation; band keratopathy; rubeosis iridis; optic neuropathy; glaucoma; chronic uveitis; migration into the lateral ventricles of the brain; posterior ciliary artery occlusion; epiretinal membranes; and episcleral, subconjunctival, and orbital foreign body granulomas. [1][2][3][4][5][6] We report a rare case of silicone oil migration into the upper eyelid that was discovered during levator advancement surgery in a patient presenting with ptosis and an extensive history of retinal procedures.…”
Section: Diffuse Siliconoma Of the Eyelidmentioning
confidence: 99%
“…However, this approach can have complications that include migration of oil into the anterior chamber, cataract, cornea dysfunction, elevated intraocular pressure, and proliferation of the epiretinal membrane. Another shortcoming is the requirement of a second operation to remove the oil [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Tıbbi malzeme üretimine uygun (medical grade) silikon yağı, enjektör içi polimetilsiloksan (Dow Corning Corp., Michigan, ABD) sürfaktanın içeriğinde %2 ila %3 oranında bulunmaktadır.3 Yapılan çalışmalarda bu miktarın gözde herhangi bir komplikasyona yol açmadığı açıklanmıştır. 4,5 İntravitreal silikon yağı, komplike retina dekolmanı cerrahisinde uzun süreli tamponlayıcı ajan olarak kullanılmakta olup glokom, katarakt, keratopati ve retinopati gibi çeşitli etkilere yol açabildiği bilinmekte olan bir ajandır. Vitreus boşluğuna verilen silikonun zamanla küçük moleküler parçacıklara ayrılması ve emülsifiye olması komplikasyon oranını arttırmaktadır.…”
Section: Discussionunclassified